Experimental Validation of Ankrd17 and Anapc10, Two Novel Meiotic Genes Predicted by Computational Models in Mice - Ray, Debjit (Biol Reprod, 2011)
Prophase is a critical stage of meiosis, during which recombination—the landmark event of meiosis—exchanges information between homologous chromosomes. The intractability of mammalian gonads has limited our knowledge on genes or interactions between genes during this key stage. Microarray profiling of gonads in both sexes has generated genome-scale information. However, the asynchronous development of germ cells and the mixed germ/somatic cell population complicate the use of this resource. To elucidate functional networks of meiotic prophase, we have integrated global gene expression with other genome-scale datasets either within or across species. Our computational approaches provide a comprehensive understanding of interactions between genes and can prioritize candidates for targeted experiments. Here, we examined two novel prophase genes predicted by computational models: Ankrd17 and Anapc10. Their expression and localization were characterized in the developing mouse testis using in situ hybridization and immunofluorescence. We found ANKRD17 expression was predominantly restricted to pachytene spermatocytes and round spermatids. ANKRD17 was diffusely distributed throughout the nucleus of pachytene cells but excluded from the XY body and other heterochromatic regions. ANAPC10 was mainly expressed in the cytoplasm of spermatogonia and leptotene and pachytene spermatocytes. These experiments support our computational predictions of Ankrd17 and Anapc10 as potential prophase genes. More importantly, they serve as a proof of concept of our integrative computational and experimental approach, which has delivered a larger candidate gene set to the broader reproductive community.